ANALISIS KEANDALAN (RELIABILITY) PADA MESIN DIGESTER (STUDI KASUS : PT. SMART TBK BATU AMPAR MILL KOTABARU) - Dwi Mulyono Putro; Qomariyatus Sholihah (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2019)
Reliability is the application of design to the component so that the component can perform its function properly. Research conducted on Digester machine that its role is quite high at PT. SMART Tbk. Batu Ampar Mill, the method used is Reliability with MTTR Method. From the calculation results obtained Digester engine reliability value in 2015 has the highest reliability value of 0,8692 at the time of calculation 329,4 hours, And in 2016 has a reliability value of 0,2972 at the time of calculation of 389,45 hours. The value of digester machine reliability in 2015 is higher than in other years, this is evidenced that the life of the Digester machine in 2015 is more dominant than in year 2016. The higher the reliability value the better the machine used in the operation process.